Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

A^2 - B^2 ,difference of two squares.?

Use difference of two squares. Determine the value of without a calculator A^2 - B^2 if 

A=2012^x + 2012^-x

B=2012^x-2012^-x.

I only know that the answer is going to be 4.

Can someone show me how I can get that answer step by step?thank you.

7 Answers

Relevance
  • ?
    Lv 7
    4 months ago
    Favorite Answer

    A^2-B^2

    =

    [2012^x+2012^(-x)]^2-[2012^x-2012^(-x)]^2

    =

    [2012^x+2012^(-x)+2012^x-2012^(-x)]

    [2012^x+2012^(-x)-2012^x+2012^(-x)]

    =

    [2(2012^x)][2(2012^-(x)]

    =

    4[2012^(x-x)]

    =

    4[2012^0]

    =

    4

  • 4 months ago

    a = 2012^(x) + 2012^(- x)

    b = 2012^(x) - 2012^(- x)

    = a² - b²

    = (a + b).(a - b)

    = { [2012^(x) + 2012^(- x)] + [2012^(x) - 2012^(- x)] }.{ [2012^(x) + 2012^(- x)] - [2012^(x) - 2012^(- x)] }

    = { 2012^(x) + 2012^(- x) + 2012^(x) - 2012^(- x) }.{ 2012^(x) + 2012^(- x) - 2012^(x) + 2012^(- x) }

    = { 2012^(x) + 2012^(x) }.{ 2012^(- x) + 2012^(- x) }

    = { 2 * 2012^(x) }.{ 2 * 2012^(- x) }

    = 2 * 2012^(x) * 2 * 2012^(- x)

    = 4 * 2012^(x) * 2012^(- x) → recall: x^(a) * x^(b) = x^(a + b)

    = 4 * 2012^(x - x)

    = 4 * 2012^(0) → recall: x^(0) = 1

    = 4

  • 4 months ago

    If A = 2012^x + 2012^-x and B = 2012^x - 2012^-x

     A^2 - B^2  = 2(2012^x + 2012^-x)

  • 4 months ago

    Remember  the difference of two squares. Any two squared numbers with a              negative between them, will factorise. 

    NB You cannot do this for a positive value. 

    Hence 

    A^2 - B^2 factors to (A - B)(A + B) 

    Note the signs. 

    Hence substituting 

    [(2012^x + 2012^-x)-(2012^x - 2012^-x)][  (2012^x + 2012^-x)+(2012^x - 2012^-x)]

    Collecting like terms inside each set of square brackets. 

    [ 2(2012^-x)][ 2(2012^x] => 

    [2 / 2012^x][2(2012^x] => 

    Cancel down by '2012^x' 

    Hence 

    [2][2] = 4 as required. 

  • How do you think about the answers? You can sign in to vote the answer.
  • Anonymous
    4 months ago

    What I'd notice is that 2012^-12 = 1/(2012^12).

    Using N = 2012^x, you have:

    A = N + 1/N

    B = N - 1/N

    You know from difference-of-squares that A² - B² = (A + B)(A - B), and those two factors

    A + B = N + 1/N + N - 1/N = 2N

    A - B =  N + 1/N - N + 1/N = 2/N

    A² - B² = (A + B)(A - B) = (2N)(2/N) = 4(N/N) = 4

    The point of using N instead of 2012^x was to show that the pattern works for *any* nonzero number N and its reciprocal 1/N.  Multiply their sum (N + 1/N) times their difference (N - 1/N) and you'll get 4.

  • Anonymous
    4 months ago

    It's been many years. Will show it step by step.

    A=2012^x + 2012^-x

    B=2012^x-2012^-x

    substitute 2012 as N

    A=N^x + N^-x

    B=N^x - N^-x

    Square each of them, add exponents when multiplying same base number, and N^0=1

    A^2=N^(2x) + N^-(2x) +2

    B^2=N^(2x)+N^-(2x) -2

    Subtract one from the other

    A^2-B^2= N^(2x) + N^-(2x) +2 - (N^(2x)+N^-(2x) -2)

    A^2-B^2= N^(2x) + N^-(2x) +2 - N^(2x)-N^-(2x) +2

    A^2-B^2= +2 +2

    A^2-B^2 = 4

     

  • ?
    Lv 7
    4 months ago

    value=(A-B)(A+B) + 2*2012^(-x)*(2012)^x=4

Still have questions? Get your answers by asking now.